(3MGTjI Ydi TQM GdgOGjI ddeHjOjs - (3eMeO TeS LjdGfjs
(3ChdgG (B:s
(3GdMeO ddg (B.. (3gPg MhGT (B... (3Ydi TQM GdgOGjI ddTGQM GdeHjOj hGdHGYK YdjgG gh Cf GdTGQM de jCJ HTjA Shi GdGYJQGVGJ hJbhjI GdGSJTcGdGJ (B.. (3GdJMbjbGJ (B...s
(3BNQgG (B:s
.. (3hbO ojOaY CjVG HCf GdLfI ePchQI HWQjb GdJeKjd hGdebUhO Cfg jdRe Schf GdLHd HedGbGJ GdLSe GdUZjQ EPG Qej Edi ahb HCfg ajg bhJg HMjK dGjecf Cf jQLY (B...s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdadSaI hGdefWbs